(3MGTjI GdLGQe Ydi GdQSGdI GdOQOjQjI aj GdHjGfs - (3GdLGQe , EHQGgje Hf eMeO Hf eMeO Hf CMeO Hf YHO GdeMSf GdMSfj GdEOjSj GdTGaYj, HQgGf GdOjf GdLGQe,J (B1271 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf QSGdI GdEeGe CHj GdHQcGJ GdJi CdagG hTQMgG ai Yde GdHjGf s
(3BNQgG (B:s
(3fSCd Gddg Cf jLYdfG eef SHbJ dg GdMSfi s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B244 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B67s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3HdGZI (B814) s
Keywords: (3GdHdGZIs